PENERAPAN MEDIA GAME INTERAKTIF BERBASIS INTERACTIVE FLAT PANEL PADA PEMBELAJARAN MATEMATIKA MATERI KONVERSI SATUAN PANJANG DI KELAS IV SD NEGERI 1 POGUNG - Bayu Purbha Sakti; Yusuf Dwinugroho; Indah Amalia Putri; Indah Luthfia Khoirunnisa; Isna Sulastri; Luthfi Tsaniyyati; Nevy Isnapratiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was conducted based on the low mathematics learning outcomes of fourth-grade students at SD Negeri 1 Pogung, particularly on the topic of length unit conversion. The objective of this study was to improve students’ mathematics learning outcomes through the implementation of an interactive game-based learning media utilizing an Interactive Flat Panel. This research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which consisted of planning, action, observation, and reflection stages conducted in two cycles. The participants were 14 fourth-grade students. Data were collected through observation, tests, and documentation and were analyzed using qualitative and quantitative descriptive techniques. The results indicated a significant improvement in students’ learning outcomes after the implementation of the interactive game media. The average score increased from 41.43 in the pretest to 58.57 in Cycle I and further improved to 80.00 in Cycle II. Learning mastery also increased from 14.29% in the pretest to 35.71% in Cycle I and reached 100% in Cycle II. In addition, students demonstrated higher levels of participation, motivation, and engagement throughout the learning process. These findings suggest that interactive game-based learning media supported by an Interactive Flat Panel can effectively enhance students’ understanding of length unit conversion concepts and improve mathematics learning outcomes in elementary school.